Fruits of 100 Angiosperms Plants of the Heart of Borneo - Meekiong, Kalu; Awang Ahmad Zahid, Awang Baim (Forest Department Sarawak, 2023)
This book is one of a series of publications under the Heart of Borneo Project Initiative for Sarawak. "The Heart of Borneo Series 15: Seeds of 100 Angiosperm Plants in the Heart of Borneo" highlights the fruits or seeds of 100 selected Angiosperm plants that were recorded or observed in the Heart of Borneo areas, with a wealth of photographs and information to assist the reader in identifying and learning about the plants. For the scientific names and families found in this book, we used current classification. Where we did not have certain information to complete the description, we adopted it from the references. It must be noted that several species that are not native to Sarawak or common pioneer species of secondary forests are also treated in this book. All flowering plants are considered, as long as they are found in Sarawak’s Heart of Borneo areas (including cultivated and introduced species). In this series, we only focus on the fruits and seeds that might be useful for identification and as self-contained as possible. Some of the terms related to and used in this book are also briefly defined in the glossary. We also do not encourage self-medication with the plant species with medicinal value described here. Also, the plant parts are usually prepared as a concoction with instructions from traditional practitioners.